Beginning SQL - Wilton, Paul, 1969- (Wrox beginning guides., 2005)
Exercises; Chapter 3: Extracting Information; The SELECT Statement; Logical Operators and Operator Precedence; Ordering Results with ORDER BY; Selecting Data from More Than One Table; Introducing NULL Data; Summary; Exercises; Chapter 4: Advanced Database Design; Normalization; Ensuring Data Validity with Constraints; Speeding Up Results with Indexes; Summary; Exercises; Chapter 5: Manipulating Data; Understanding SQL Arithmetic; Introducing String Functions; Converting Different Data Types; Re-examining NULL; Using INSERT INTO with the SELECT Statement; Summary; Exercises